Chronic rhinosinusitis with nasal polyposis: the role of personalized and integrated medicine - Passali, Desiderio; Bellussi, Luisa Maria; Damiani, Valerio; Tosca, Maria Angela; Motta, Gaetano; Ciprandi, Giorgio (Acta Biomedica Atenei Parmensis, 2020)
Chronic rhinosinusitis with nasal polyposis (CRSwNP) is a frequent disorder. From a clinical and an immunopathological point of view, different phenotypes and endotypes have been identified. The frequent comorbidity with asthma allowed to pave the way to the use of biological agents for the treatment of CRSwNP. Biological agents are targeted to antagonize IgE, interleukin (IL) 4, IL-5, and IL-13 at present. However, a correct and appropriate workup is mandatory, mainly concerning the exact definition of the specific pheno-endotype. The preliminary outcomes are promising, even though there is a need for well-established indications, criteria of responsiveness, duration, and safety. On the other hand, this personalized medicine could be fruitfully integrated with gold-standard medications, such as intranasal corticosteroids. As CRSwNP is a chronic disorder, treatment should be long-lasting, so complementary anti-inflammatory treatments could be opportunely integrated and/or alternated to steroids.